Factors Affecting Customer Satisfaction with The last- mile Delivery Service of The Food and Beverage Industry E-Commerce in Hanoi City - NGUYEN, THAO VY; NGUYEN, BAO CHAU; CAO, THU HANG; NGUYEN, THI NGA; NGUYEN, HOANG MINH HOAI; DINH, LE HAI HA; NGUYEN, XUAN HUNG (The journal of contemporary issues in business and government, 2021)
The purpose of this article is to analyze the factors affecting customer satisfaction with the use of last-mile delivery service in the food and beverage industry in e-commerce in Hanoi.The authors examine the impact of factors on customer satisfaction from 2015 to 2021 using the SERVQUAL service quality model combined with the SERVPERF perceived level model, and the American customer satisfaction index model - ACSI. The results show a relatively significant impact of several factors such as reliability, assurance, empathy and perceived value. In addition, income and gender factors also affect customer satisfaction.